Pengelolaan Manajemen Modern dalam Mewujudkan Good Corporate Governance: Optimalisasi Pencapaian Tujuan Perusahaan - Ignatius Edward Riantono (Bina Nusantara University, 2014)
Implementation and management of good corporate governance, better known by the term Good Corporate Governance, is a concept that emphasizes the importance of shareholders to obtain true, accurate, and punctual information. In this era of global competition state borders are no longer a barrier to competition; only companies that implement good corporate governance (GCG) are capable of winning the competition. GCG is a must in order to establish conditions of tough and sustainable company. GCG is necessary to create a system and a strong corporate structure so as to become world class company. Good Corporate Governance is basically a system (input, process, and output) and a set of rules that govern the relationship between various parties (stakeholders); especially in the narrow sense, the relationship between the shareholders, the board of commissioners, and the board of directors in order to achieve corporate objectives. Good Corporate Gorvernance encloses to regulate these relationships and prevent significant errors in the company's strategy and to ensure the errors occur can be improved immediately.